Should physical activity recommendations be ethnicity-specific? Evidence from a cross-sectional study of South Asian and European men. - Carlos A Celis-Morales (Public Library of Science (PLoS), 2013)
Background Expert bodies and health organisations recommend that adults undertake at least 150 min.week(-1) of moderate-intensity physical activity (MPA). However, the underpinning data largely emanate from studies of populations of European descent. It is unclear whether this level of activity is appropriate for other ethnic groups, particularly South Asians, who have increased cardio-metabolic disease risk compared to Europeans. The aim of this study was to explore the level of MPA required in South Asians to confer a similar cardio-metabolic risk profile to that observed in Europeans undertaking the currently recommended MPA level of 150 min.week(-1). Methods Seventy-five South Asian and 83 European men, aged 40-70, without cardiovascular disease or diabetes had fasted blood taken, blood pressure measured, physical activity assessed objectively (using accelerometry), and anthropometric measures made. Factor analysis was used to summarise measured risk biomarkers into underlying latent 'factors' for glycaemia, insulin resistance, lipid metabolism, blood pressure, and overall cardio-metabolic risk. Age-adjusted regression models were used to determine the equivalent level of MPA (in bouts of ≥ 10 minutes) in South Asians needed to elicit the same value in each factor as Europeans undertaking 150 min.week(-1) MPA. Findings For all factors, except blood pressure, equivalent MPA values in South Asians were significantly higher than 150 min.week(-1); the equivalent MPA value for the overall cardio-metabolic risk factor was 266 (95% CI 185-347) min.week(-1). Conclusions South Asian men may need to undertake greater levels of MPA than Europeans to exhibit a similar cardio-metabolic risk profile, suggesting that a conceptual case can be made for ethnicity-specific physical activity guidance. Further study is needed to extend these findings to women and to replicate them prospectively in a larger cohort.